Anodes based on Pt doped titanium sub-oxides - Kasian, O. I.; Luk'Yanenko, T. V.; Amadelli, Rossano; Velichenko, A. B. (ECS Transactions, 2013)
Effects of thermal treatment and amount of electrodeposited Pt on electrocatalytic activity of materials based on platinized Ebonex® were investigated. Surface morphology, phase and chemical composition were found to be strongly depended on temperature of electrode preparation. Crystallite size of platinum coating was shown to increase with temperature of thermal treatment. At the same time decrease in strains in coating with temperature was observed providing better mechanical stability of the thermally treated electrodes. Materials based on platinized Ebonex® were shown to be n-type semiconductors that affect their electrochemical behavior. An increase in the flatband potential with temperature, and the donor concentration decrease were observed due to both oxidation of Pt and TiO2 formation. Some of platinized Ebonex® anodes could be recommended for application in a trivalent chromium electroplating bath owing to low rates of Cr(III) electrooxidation and extended service life. © 2014 The Electrochemical Society.
CRIS-Team Scopus Importer:2023-03-07